Internal Validation of Organizational Well-Being Measurement Tools in the Context of Higher Education Using Confirmatory Factor Analysis - Sukmarani, Sukmarani (Kuras Institute, 2024)
Organizational welfare is a topic that is currently being researched and developed due to its impact on individuals and organizations in efforts to improve performance. This study aims to test the psychometric construct of the Organizational Welfare measurement tool in the context of higher education, developed by researchers based on the theory of Prilleltensky & Prilleltensky (2006). The sample consists of 432 participants, comprising lecturers and employees of private universities in Jakarta (50% lecturers and 50% employees). The Organizational Welfare measurement tool consists of 64 items that measure three dimensions: Effective Environment, Reflective Environment, and Affective Environment. Data analysis was conducted using Confirmatory Factor Analysis with Lisrel 8.8 software, and internal consistency was tested using Cronbach's alpha. The results showed that the three dimensions of the Organizational Welfare measurement tool had a fit model (meeting the model suitability criteria as per Hu & Bentler, 1999) and Cronbach's alpha coefficients ranging from 0.88 to 0.92. In total, 63 items were found to be valid, while 1 item was invalid due to having a t-value of less than 1.96.